Model pengendalian kualitas produk cover bottom (electronic part) menggunakan metode lean six sigma - Dendhy Indra Wijaya; Fauzi Khair (Universitas Mercu Buana, 2019)
Company shall give full attention to the quality of the products. In the electronics industry, quality control is the key to gain the loyalty of the customer. This is the basis for making improvement at the production activities, especially in controlling the quality in order to reduce the problem of scratch on the cover bottom using the six sigma DMAIC method. The purpose of this research is to analyze the factor that will cause defect to the product. The aimed target is to reduce the lower problem of defective products cover bottom 50%, it also to get the best result where previous defective products amounted to 8183 ppm has downed to 291 ppm and the level of the previous sigma 3,89σ rose to 4,94σ, the target is 4,14σ. This was result an exceed achievement from the Company’s target more than 50%. Six Sigma is the most effective tools at the present time, this will affect to eliminate defects, cut the time of making the product, eliminate unnecessary costs and the principal concept of science to support the sustainability of business which is focused on improving quality and customer satisfaction. The key success of improving quality depends on the ability to identify and solve the problems. This application may be useful and align with the company's philosophy, so that it can be expected to get the final outcome of the company.